Literacy Resource Directory : Prevention Activities in Quebec - Seys, Wendy (Literacy Volunteers of Quebec, 2004)

Report from the Executive Director - Hook, Deborah (Quebec Community Groups Network (QCGN), 2004)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2004)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

Remote Site Information Technology Assessment for the Municipality of Bonne-Esperance Lower North Shore, Quebec - Coasters Association (2004)
Information technologies (computers, Internet, etc.) are an essential component of modern economic development strategies. The Lower North Shore has lagged behind other areas in terms of equipment, infrastructure and human resource capacity for using information technologies as an integral part of their community development efforts (i.e. no hi-speed access.) Recent innovations in this area allow for the reception of hi-speed (broadband) Internet reception via satellite; with establishment of local area networks (LANs) connected to each satellite point-of-delivery, the prospect exists for significant improvements to the information technology capacity of remote locations such as MBE, as well as local revenue generation from service provision once the LAN is established.

The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)